Association of fall risk in older adults between gender, fear of falling and autonomy - Rios, T (2019)
Aging is a natural process of the individual and is associated with a decline in physical and mental function. Given the high prevalence of older adults worldwide, it becomes ppropriated to identify the consequences of this reduction. The falls appear as a consequence more common in this specific population, which triggers the need to identify the different risk factors, in order to prevent them and create intervention programs in that way.